2014
DOI: 10.2147/ijn.s64708
|View full text |Cite|
|
Sign up to set email alerts
|

Preparation of bufalin-loaded pluronic polyetherimide nanoparticles, cellular uptake, distribution, and effect on colorectal cancer

Abstract: A large number of studies have shown that bufalin can have a significant antitumor effect in a variety of tumors. However, because of toxicity, insolubility in water, fast metabolism, short half-life, and other shortcomings, its application is limited in cancer therapy. In this study, we explored the anti-metastatic role of bufalin-loaded pluronic polyetherimide nanoparticles on HCT116 colon cancer-bearing mice. Nanoparticle size, shape, drug loading, encapsulation efficiency, and in vitro drug release were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…BU, which is extracted from Chinese toad venom, is a toxic ligand with maximal antitumour effects and is a bufadienolide[ 25 27 ]. Modern research has found BU to have strong anti-tumour effects.…”
Section: Discussionmentioning
confidence: 99%
“…BU, which is extracted from Chinese toad venom, is a toxic ligand with maximal antitumour effects and is a bufadienolide[ 25 27 ]. Modern research has found BU to have strong anti-tumour effects.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, novel bufalin formulations have shown promising efficacy in xenograft tumor models [ 7 , 30 , 31 ]. Randomized, double-blind, placebo-controlled human trials are now required to assess the therapeutic value of bufalin in various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Bufalin is a digoxin-like active component of Chan Su, a traditional Chinese medicine produced from the skin and parotid venom glands of the toad [ 1 ]. Bufalin exhibits potent antitumor activities in many human cancers such as leukemia [ 2 , 3 ], hepatocellular carcinoma [ 4 , 5 ], gastric cancer [ 6 ], and colorectal cancer [ 7 ]. Moreover, bufalin sensitizes drug-resistant cancers to various chemotherapeutic agents [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Body (Fig. 1A ) length 16.0, carapace 7.9 long, 5.0 wide, abdomen 8.8 long, 5.8 wide (data from original description by Yin et al 1997 : 64). Carapace dark reddish brown.…”
Section: Taxonomymentioning
confidence: 99%